RETRACTED: Analisis Penguasaan Konsep Gerak Parabola yang Belajar dengan Modeling Instruction Disertai Formative-Authentic E-Assessment - Siti Imtinan; Sentot Kusairi; Purbo Suwasono (Universitas Negeri Malang, 2020)
Following a rigorous, carefully concerns, and considered review of the article published in JRPF (Jurna Riset Pendidikan Fisika) to article entitled “Analisis Penguasaan Konsep Gerak Parabola yang Belajar dengan Modeling Instruction Disertai Formative-Authentic E-Assessment” Vol. 5, No. 1, pp. 38–45, 2020.This paper has been found to be in violation of the JRPF (Jurna Riset Pendidikan Fisika) and has been retracted. The document and its content has been removed from JRPF (Jurnal Riset Pendidikan Fisika), and reasonabel effort should be made remove all references to this article.